Konstruksi Mitos dalam Lirik Lagu Arab Kontemporer: Analisis Semiotika Roland Barthes terhadap Fi'Il Amr dalam Album Aseer Ahsan - Surya Maulana; Rohanda Rohanda; Yadi Mardiansyah (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
Contemporary Islamic pop music has become a global medium for disseminating spiritual and cultural values, yet the semiotic mechanisms constructing these values remain critically underexplored. This study analyzes myth formation through fi'il amr (imperative verbs) in Humood AlKhudher's album Aseer Ahsan using Roland Barthes' semiotic framework, specifically focusing on the process of depoliticization. Employing a descriptive qualitative method, 39 instances of fi'il amr were identified and heuristically classified using Halliday's transitivity system (Material, Behavioral, Mental, Verbal, Relational) before Barthesian interpretation. The findings reveal that Material (38.5%) and Behavioral (35.9%) categories dominate. Across these categories, a unified myth emerges: the